Characterization of glutamate carboxypeptidase 2 orthologs in trematodes - Jedlickova, Lucie; Peterkova, Kristyna; Boateng, Enoch Mensah; Ulrychova, Lenka; Vacek, Vojtech; Kutil, Zsofia; Jiang, Zhenze; Novakova, Zora; Snajdr, Ivan; Kim, Juan; O'Donoghue, Anthony J; Barinka, Cyril; et al. (Parasites & vectors, 2022)
BACKGROUND: Glutamate carboxypeptidase 2 (GCP2) belongs to the M28B metalloprotease subfamily encompassing a variety of zinc-dependent exopeptidases that can be found in many eukaryotes, including unicellular organisms. Limited information exists on the physiological functions of GCP2 orthologs in mammalian tissues outside of the brain and intestine, and such data are completely absent for non-mammalian species. Here, we investigate GCP2 orthologs found in trematodes, not only as putative instrumental molecules for defining their basal function(s) but also as drug targets. METHODS: Identified genes encoding M28B proteases Schistosoma mansoni and Fasciola hepatica genomes were analyzed and annotated. Homology modeling was used to create three-dimensional models of SmM28B and FhM28B proteins using published X-ray structures as the template. For S. mansoni, RT-qPCR was used to evaluate gene expression profiles, and, by RNAi, we exploited the possible impact of knockdown on the viability of worms. Enzymes from both parasite species were cloned for recombinant expression. Polyclonal antibodies raised against purified recombinant enzymes and RNA probes were used for localization studies in both parasite species. RESULTS: Single genes encoding M28B metalloproteases were identified in the genomes of S. mansoni and F. hepatica. Homology models revealed the conserved three-dimensional fold as well as the organization of the di-zinc active site. Putative peptidase activities of purified recombinant proteins were assayed using peptidic libraries, yet no specific substrate was identified, pointing towards the likely stringent substrate specificity of the enzymes. The orthologs were found to be localized in reproductive, digestive, nervous, and sensory organs as well as parenchymal cells. Knockdown of gene expression by RNAi silencing revealed that the genes studied were non-essential for trematode survival under laboratory conditions, reflecting similar findings for GCP2 KO mice. CONCLUSIONS: Our study offers the first insight to our knowledge into M28B protease orthologs found in trematodes. Conservation of their three-dimensional structure, as well as tissue expression pattern, suggests that trematode GCP2 orthologs may have functions similar to their mammalian counterparts and can thus serve as valuable models for future studies aimed at clarifying the physiological role(s) of GCP2 and related subfamily proteases.
Keywords: NAALADase; myši; Prostate specific-membrane antigen; RNA in situ hybridization; savci; Animals; Mice; Platyhelminth; Folate hydrolase; Mammals; Immunohistochemistry; M28B metalloproteases; proteasy; Schistosoma mansoni; Fasciola hepatica; zvířata; Peptide Hydrolases; Trematoda